2015
DOI: 10.4238/2015.august.7.26
|View full text |Cite
|
Sign up to set email alerts
|

Association of AGTR1 gene A1166C polymorphism with the risk of heart failure: a meta-analysis

Abstract: ABSTRACT. The aim of this study was to investigate the correlation between the A1166C polymorphism in the angiotensin II type 1 receptor (AT1R) gene and heart failure (HF) risk using meta-analysis. The PubMed database was searched, and data were extracted independently by two reviewers. Odds ratios (ORs) with corresponding 95% confi dence intervals (CIs) were used to assess the strength of the associations. Statistical analysis was performed using the STATA 12.0 software. The results of the metaanalysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As a hepatic manifestation of the metabolic syndrome, we can suppose that NAFLD may promote the development of atherosclerosis [ 5 , 6 ]. Some reports demonstrated that because of the promoting effect on CVD, NAFLD patients were at high risk of death [ 8 , 10 ]. Nowadays many epidemiological and clinical studies focus on the association between NAFLD and CAD [ 19 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a hepatic manifestation of the metabolic syndrome, we can suppose that NAFLD may promote the development of atherosclerosis [ 5 , 6 ]. Some reports demonstrated that because of the promoting effect on CVD, NAFLD patients were at high risk of death [ 8 , 10 ]. Nowadays many epidemiological and clinical studies focus on the association between NAFLD and CAD [ 19 24 ].…”
Section: Discussionmentioning
confidence: 99%